IMMOBILIZATION OF PAPAIN ON CHITOSAN Imobilisasi Papain Pada Kitosan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT In this study, papain was immobilized on chitosan with Mg(l/) cosslinked agent. Studies on free and immobilizedpapain systems for determination of optimumpH, optimum temperatur, thermal stability and reusability were carried out. The results showed that free papain had optimumpH 6.5 and optimum temperature 55°C while the immobile papain had optimum pH 8 and optimum temperature 80 °C. The thermal stability of the immobilized papain, relative to that of the free papain, was markedly increased. The immobilized papain can be reused for at least six times. Keywords: papain, immobilization,chitosan